PENINGKATAN ASUPAN MINERAL Fe DAN VITAMIN C PADA TOKOH MASYARAKAT MELALUI PENYULUHAN DENGAN MEDIA BOOKLET - Slamet Iskandar Iskandar; Almira Sitasari; Diana Andriyani Pratamawati; Endah Martati (Media Gizi Mikro Indonesia, 2023)
Background: Consuming food that is not diverse can cause nutrient intake to be deficient and unbalanced, which will affect an individual's nutritional status. Mineral deficiencies can cause health problems such as goiter, osteoporosis, osteomalacia and anemia. Meanwhile, a lack of Vitamin C will cause dry skin, wounds that take longer to heal, bleeding gums, mouth ulcers and anemia. Fulfilling mineral and vitamin needs can be obtained from consuming animal and vegetable foods. One effort to increase mineral and vitamin intake is by conducting outreach in the community. Objective: To know the increased intake of minerals (Fe) and vitamin C figures of the community leaders through counseling using booklet media. Methods: This study used a cohort design with one group pretest and posttest without control. The sample for this research was one hundred community leaders from Jetis District, Bantul Regency. Data on mineral and vitamin intake was collected using food recall. Data analysis was carried out using the Wilcoxon Signed Rank Test.. Results: The average initial tomas mineral intake was 5.15 ± 4.28 mg. The average final tomas mineral intake was 7.76 ± 4.77 mg. The average initial intake of vitamin C for Tomas was 22.56 ± 21.78 mg. The average final intake of vitamin C was 74.60 ± 78.50 mg. The average initial knowledge of Thomas was 44.85 ± 13.72. The average knowledge of final Tomas was 71.55 ± 19.65. The average initial attitude was 56.31 ± 3.48. The average final attitude was 71.98 ± 5.04. Conclusion: There was an increase in Tomas' knowledge, Tomas' attitude, Tomas' mineral intake, and Tomas' vitamin C intake before and after counseling using booklet media. Keywords: Booklet, mineral, Vitamin C, Tomas ABSTRAK Latar Belakang : Konsumsi pangan yang tidak beraneka ragam dapat menyebabkan asupan zat gizi menjadi kurang dan tidak seimbang, sehingga akan berpengaruh pada status gizi individu. Defisiensi mineral dapat menyebabkan gangguan kesehatan seperti gondok, osteoporosis, osteomalasia, dan anemia. Sedangkan kekurangan Vitamin C akan menyebabkan kulit kering, luka lebih lama sembuh, gusi berdarah, sariawan, dan anemia. Pemenuhan kebutuhan mineral dan vitamin dapat diperoleh dari konsumsi pangan hewani maupun nabati. Salah satu upaya untuk meningkatkan asupan mineral dan vitamin adalah dengan melakukan penyuluhan di Masyarakat. Tujuan : Mengetahui peningkatan asupan mineral (Fe) dan vitamin C tokoh masyarakat melalui penyuluhan dengan media booklet. Metode : Penelitian ini menggunakan disain kohort dengan one group pretest and posttest without control. Sampel penelitian ini adalah seratus tokoh masyarakat dari Kecamatan Jetis Kabupaten Bantul. Data tentang asupan mineral dan vitamin dikumpulkan dengan food recall. Analisis data dilakukan dengan Wilcoxon Signed Rank Test. Hasil : Rata-rata asupan mineral tomas awal adalah 5,15 ± 4,28 mg. Rata-rata asupan mineral tomas akhir adalah 7,76 ± 4,77 mg. Rata-rata asupan vitamin C tomas awal adalah 22,56 ± 21,78 mg. Rata-rata asupan vitamin C tomas akhir adalah 74,60 ± 78,50 mg. Rata-rata pengetahuan tomas awal adalah 44,85 ± 13,72. Rata-rata pengetahuan tomas akhir adalah 71,55 ± 19,65. Rata-rata sikap tomas awal adalah 56,31 ± 3,48. Rata-rata sikap tomas akhir adalah 71,98 ± 5,04. Kesimpulan : Ada peningkatan pengetahuan tomas, sikap tomas, asupan Mineral tomas, dan asupan vitamin C tomas sebelum dan sesudah penyuluhn dengan media booklet. Kata Kunci : Booklet, Asupan mineral, Asupan Vitamin C, Tomas